2009
DOI: 10.1007/s10815-009-9319-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of high ovarian response to controlled ovarian hyperstimulation: anti-Müllerian hormone versus small antral follicle count (2–6 mm)

Abstract: Purpose To evaluate the predictive value of basal serum anti-müllerian hormone level and small antral follicle count for high ovarian response to controlled ovarian hyperstimulation. Methods A total of 159 patients were prospectively included. Basal serum anti-müllerian hormone and small antral follicle count (2-6 mm) were measured. Results Small antral follicle count and anti-müllerian hormone have similar predictive accuracy for high ovarian response with area under curve of 0.961 and 0.922, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 40 publications
4
36
0
5
Order By: Relevance
“…10,11 From the present study, we conclude that age and AMH have negative correlation (r-0.266) ( Figure 1). …”
Section: -40supporting
confidence: 54%
See 1 more Smart Citation
“…10,11 From the present study, we conclude that age and AMH have negative correlation (r-0.266) ( Figure 1). …”
Section: -40supporting
confidence: 54%
“…Patients were studied with respect to total number of oocytes, number of mature oocytes, duration of stimulation, total dose of gonadotropins, peak E2 levels, number of embryos and Grade A embryos. According to number of oocytes retreived, patients were divided into poor responders (<3 oocytes) normal responders (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and hyperresponders (>20).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the statistical model developed evidenced that the decrease in plasma AMH concentrations with age is more marked in the low AFC group compared with the high one. In this regard, AFC and AMH are widely used to predict ovarian reserve and ovarian response to controlled stimulation with exogenous gonadotropins for assisted reproductive technologies (ARTs) treatments (La Marca et al 2007, Aflatoonian et al 2009, Fleming et al 2015; moreover, a better prediction of ovarian responsiveness is achieved when using AMH, AFC, and age together (Brodin et al 2015). Taken together, these results immediately suggest that high AFC and AMH concentrations in the early prepubertal period may represent a precocious marker of the ovarian reserve of a given individual, considering that the quantity and quality of non-growing follicles in the ovary is positively associated with the number of growing follicles, plasma AMH concentrations, and reproductive life-span .…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by another study that showed that small AFC (2-6 mm) and AMH are equally accurate predictors of ovarian response to controlled ovarian hyperstimulation (17). In addition to being a good marker for the quantity of follicles, AMH is also suggestive of the quality of the remaining oocytes (18).…”
Section: Assisted Reproductionmentioning
confidence: 66%